"The Malay Garden" is "The Malaysian Garden (MGC)": The Reality and Challenges of Establishing a National Identity - Zakaria, Ahmad Zamil; Dali, Melasutra Md; Hussein, Hazreena (International Journal of Psychosocial Rehabilitation, 2020)
The Malaysian Garden Concept (MGC) is an initiative by the National Landscape Department (NLD) to develop a garden concept that will one day achieve its fame, as the garden concepts are well known today. A comparative study was to determine the level of MGC criteria applies to public parks built by the NLD. The selected case studies were from a public park built after the MGC guidelines established in 2009 (n = 6). 5 MGC experts were interviewed in this study to confirm the issues raised. For the record, planning to create these guidelines took a long time and involved various parties associated with the profession of Landscape Architect. The methodology of the study using observation and interview techniques (selected through criterion sampling method). From the research conducted, researchers have found that the level of compliance with the MGC guidelines is worrisome, and possibly no effort to uphold this concept by the responsible party. There are 3 criteria that hard to be implemented by most of these public parks are Architectural structure & local elements; Culture & Heritage; and High Intrinsic Value. This research has shown that it is not easy to apply a "heritage & culture" principles in landscape design, especially to a multiracial and multicultural country like Malaysia.